1996
DOI: 10.1128/aac.40.6.1561
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of bacteria to danofloxacin by temperate prophages

Abstract: Danofloxacin (CP-76,136) is in a class of agents that inhibit DNA gyrase and trigger induction of the SOS response and temperate bacteriophages. Killing studies against the bovine pathogen Pasteurella haemolytica demonstrated that danofloxacin exhibits particularly rapid killing kinetics. Here, lysogenic Escherichia coli bearing lambda is found to be more sensitive to danofloxacin than nonlysogenic E. coli. Danofloxacin exposure also induced a prophage in P. haemolytica. The potency of danofloxacin against lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 8 publications
1
17
1
Order By: Relevance
“…Basically, the las system regulates the two others (Latifi et al, 1996; Pesci et al, 1997), and while rhl inhibits pqs, pqs is able to activate rhlI . At the same time pqs regulates eDNA release, membrane vesicles production and prophage induction (Figure 1; Froshauer et al, 1996; Mashburn and Whiteley, 2005; Allesen-Holm et al, 2006). …”
Section: Edna Production In Cultured Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Basically, the las system regulates the two others (Latifi et al, 1996; Pesci et al, 1997), and while rhl inhibits pqs, pqs is able to activate rhlI . At the same time pqs regulates eDNA release, membrane vesicles production and prophage induction (Figure 1; Froshauer et al, 1996; Mashburn and Whiteley, 2005; Allesen-Holm et al, 2006). …”
Section: Edna Production In Cultured Microorganismsmentioning
confidence: 99%
“…Specifically, it depends on the las and pqs systems (Renelli et al, 2004; Nakamura et al, 2008). The pqs system is not only implicated in eDNA production, as quinolones are well-known for triggering prophage induction and cause cell lysis (Froshauer et al, 1996). Considering that the motility is necessary for phages propagation, Allesen-Holm et al (2006), analyzed a motility mutant and concluded that the PQS mediates prophage induction and the flagella/pili-dependent phage propagation are involved in eDNA release.…”
Section: Edna Production In Cultured Microorganismsmentioning
confidence: 99%
“…Previous studies demonstrated that the presence of prophages increased the sensitivity of M. haemolytica to danofloxacin, and exposure to this antimicrobial induced prophage production (Froshauer et al . ). We selected 66 M. haemolytica isolates with high and low levels of enrofloxacin sensitivity based on disc diffusion assays and found no correlation between presence of inducible phages and the sensitivity of M. haemolytica to this antibiotic.…”
Section: Discussionmentioning
confidence: 97%
“…Both danofloxacin and enrofloxacin inhibit bacterial DNA gyrase (Froshauer et al . ), resulting in DNA damage during replication. Many bacteria possess an SOS‐response system which is an inducible DNA repair system that allows bacteria to overcome DNA damage (Foster ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation